2021
DOI: 10.1111/jac.12576
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen supplement attenuates drought stress for non‐leguminous hybrid plant fescue and does not affect nitrogen‐fixing alfalfa

Abstract: Estimated anthropogenic global warming is currently increasing at 0.2°C per decade and will likely reach 1.5°C between 2030 and 2050 (Pishva et al., 2020). As a result, the evapotranspiration rate is enhanced and therefore increases the likelihood of drought stress in plants (Yang et al., 2010). Drought frequency and intensity in drylands is projected to increase from 1% to 30% by 2100 (Dai, 2013). Globally, about one-third of the land area is affected by drought (Pishva et al., 2020). It is a major threat and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 78 publications
2
0
0
Order By: Relevance
“…N, being a key component of proteins, chlorophyll, and Rubisco affected the whole metabolism of plants during cold stress. Reduced chlorophyll contents in turfgrasses under limited N fertilization and abiotic stress conditions were also previously reported by (Shen et al, 2020;Janusǩaitienėet al, 2021). The enhanced levels of photosynthetic pigments in response to N, P, and K could also be ascribed to the regulation of enzymatic and nonenzymatic antioxidants defense systems and decreased lipid peroxidation, cell membrane damage, and H 2 O 2 in this study, as confirmed by the correlation analysis.…”
Section: Photosynthetic Pigmentssupporting
confidence: 90%
“…N, being a key component of proteins, chlorophyll, and Rubisco affected the whole metabolism of plants during cold stress. Reduced chlorophyll contents in turfgrasses under limited N fertilization and abiotic stress conditions were also previously reported by (Shen et al, 2020;Janusǩaitienėet al, 2021). The enhanced levels of photosynthetic pigments in response to N, P, and K could also be ascribed to the regulation of enzymatic and nonenzymatic antioxidants defense systems and decreased lipid peroxidation, cell membrane damage, and H 2 O 2 in this study, as confirmed by the correlation analysis.…”
Section: Photosynthetic Pigmentssupporting
confidence: 90%
“…Our previous study also indicated significantly reduced efficiency with which an electron can move from the reduced intersystem electron acceptors to the PSI end electron acceptors (Delta[Ro]) and the time for maximum fluorescence (t for Fm) in alfalfa as well as increased Delta(Ro) in hybrid fescue, subjected to the single drought. These changes confirm higher single drought resistance of hybrid fescue compared to alfalfa (Januškaitienė, Kacienė, et al, 2021). This finding is consistent with other studies, as drought is one of the major constraints for legumes (Nadeem, Li, et al, 2019); alfalfa was also found to be more sensitive to drought than Festulolium by Staniak and Harasim (2018).…”
Section: Discussionsupporting
confidence: 59%